Residue hydroprocessing catalyst and process for its preparation

CN122999216APending Publication Date: 2026-10-30GUANGRAO SHENGTAI WEIYE CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611514245.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但该技术主要着眼于通过载体成孔以及预干燥、水洗处理主动形成特定的活性金属梯度分布,对于Ni、Mo组分在浸渍液中的预络合稳定状态以及后续干燥过程中因液相迁移导致的局部富集缺少连续协同调控,在提高Ni、Mo组分整体分布均匀性以及降低孔口局部聚集方面仍具有进一步改善空间

Benefits of technology

1、本发明中,通过在氧化铝载体初步焙烧后设置孔道调控处理、孔结构固定的局部重构工艺,利用多羧基调控液对氧化铝载体中限制大分子扩散的狭窄孔道区域及其孔壁表面的Al—OH位点进行有限络合处理,再通过碳酸氢铵调节孔道内局部液相环境并进行高温放置,有利于经络合处理的铝物种在孔壁区域重新分布和固定,从而形成孔道局部处理、孔内物种迁移以及孔结构固定的调控过程。与单纯扩大整体孔径相比,该工艺能够优先改善限制渣油中沥青质及大分子组分扩散的狭窄孔道,提高孔道连通性和有效传质能力,同时减少过度酸蚀造成的载体骨架损伤,有利于兼顾催化剂的大孔传质性能与机械稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999216A_ABST
    Figure CN122999216A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of petroleum refining catalyst, in particular to a residual oil hydrogenation catalyst and a preparation process thereof.In the present application, after the preliminary calcination of the alumina carrier, a pore channel regulation treatment and a local reconstruction process of fixed pore structure are arranged, a multi-carboxyl pore channel regulation liquid is used to carry out limited complex treatment on the narrow pore channel area limiting macromolecular diffusion in the alumina carrier and the Al-OH site on the pore wall surface, then the local liquid phase environment in the pore channel is adjusted by ammonium bicarbonate and is placed at high temperature, which is beneficial to the redistribution and fixation of the aluminum species subjected to the complex treatment in the pore wall area, meanwhile, a complex impregnation process of pre-complexing of nickel component, post-introduction of molybdenum component and impregnation in several times and a gradient drying process are adopted, which reduces the aggregation of large-size metal salt and the pore blockage in the subsequent drying and calcination process, and is beneficial to improving the effective utilization degree of active metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of petroleum refining catalyst technology, specifically to a residue oil hydrogenation catalyst and its preparation process. Background Technology

[0002] Residue hydrotreating catalysts are mainly used in the residue hydrotreating process. They form a catalytic system with hydrotreating activity by supporting active metal components such as nickel and molybdenum on a support. Since the residue hydrotreating process requires balancing mass transfer of larger molecular components within the catalyst channels with the effective utilization of active metal components, the pore volume, pore size distribution, and pore connectivity of the catalyst support, as well as the uniformity of the dispersion of Ni and Mo active components within the support, all significantly affect the catalyst's performance.

[0003] In existing technologies, for example, Chinese invention patent CN1782031A discloses a catalyst for hydrodemetallization of residue oil and its preparation method. This method uses bimodal porous alumina as a support and loads molybdenum and / or tungsten, as well as nickel and / or cobalt active metal components. By designing the pore size distribution of the alumina support, it provides corresponding reaction channels while ensuring the diffusion of large molecular reactants, thereby improving the hydrodemetallization performance of residue oil. However, this technology mainly constructs the overall bimodal porous structure during the alumina support preparation and molding stages. It lacks further targeted control over the localized narrow pore areas that exist after the support has been molded and calcined. Therefore, there is still room for optimization in further improving pore connectivity while ensuring the stability of the support framework.

[0004] Chinese invention patent CN106914249B discloses a catalyst for hydrodemetallization of residual oil and its preparation method. The method involves preparing a support by adding a non-acidic binder and a composite pore-expanding agent to boehmite, followed by active metal impregnation, pre-drying, water washing, re-drying, and calcination. This results in a catalyst exhibiting both a bimodal pore structure and a gradient distribution of active metals that gradually decreases from the particle center to the outer surface. However, this technology primarily focuses on actively forming a specific active metal gradient distribution through support pore formation and pre-drying and water washing. It lacks continuous and synergistic control over the pre-complexed stable state of Ni and Mo components in the impregnation solution and the local enrichment caused by liquid phase migration during subsequent drying. Further improvement is needed in enhancing the overall uniformity of Ni and Mo component distribution and reducing local aggregation at the pore openings. Summary of the Invention

[0005] The purpose of this invention is to provide a residue oil hydrogenation catalyst and its preparation process. The residue oil hydrogenation catalyst prepared by this invention not only has a good pore structure and pore connectivity, but also has excellent active metal dispersion uniformity and mechanical stability, effectively improving the overall performance of the residue oil hydrogenation catalyst.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a process for preparing a residue oil hydrogenation catalyst, comprising the following steps: S1: Carrier molding: Boehmite and guar gum powder are mixed at a mass ratio of 100:(2-4), and 55-75% of the mass of boehmite in deionized water and 12-20% of the mass of boehmite in nitric acid aqueous solution with a mass fraction of 5-10% are added. The mixture is stirred at 300-500 rpm for 20-40 min, kneaded, extruded, dried at 100-120℃ for 6-10 h, and calcined at 520-580℃ for 3-5 h to obtain the first carrier; S2: Pore control treatment: Add 3.5-5.5 times its mass of deionized water and 2-4% of its mass of polycarboxylic acid pore control solution to the first carrier, and treat at 50-65℃ and 60-100rpm for 30-60min. After treatment, filter and remove the free liquid on the surface of the first carrier to obtain the treated carrier material. The polycarboxylic acid pore control solution is prepared by mixing lactobionic acid pretreatment solution, tetrasodium iminodisuccinate and gluconate-δ-lactone in aqueous phase. S3: Pore structure fixation: Spray 4-8% ammonium bicarbonate aqueous solution onto the treatment carrier material, place it at 60-75℃ and 85-95% relative humidity for 1-2 hours, wash it with 2-3 times the mass of deionized water, dry it at 100-120℃ for 4-8 hours, and then calcine it at 450-520℃ for 2-4 hours to obtain the second carrier; S4: Complexation Impregnation: Nickel nitrate hexahydrate is added to the nickel complexation additive solution to obtain a metal mixture solution, which is set aside for use. Ammonium heptamolybdate tetrahydrate is dissolved in 2.5-4.5 times its mass of deionized water to obtain an ammonium heptamolybdate solution. The metal mixture solution is added to the ammonium heptamolybdate solution, and the pH is adjusted to 4.8-5.8 with ammonia water to obtain an impregnation solution. The impregnation solution is sprayed into the second carrier in two stages to obtain the impregnated wet material. The nickel complexation additive solution is prepared by mixing tetrasodium diacetate of glutamic acid, sodium gluconate and ammonium acetate in an aqueous phase. S5: Gradient drying: The impregnated wet material is placed at 35-45℃ and 88-95% relative humidity for 2-4 hours, then treated at 50-65℃ and 60-75% relative humidity for 1.5-3 hours, then treated at 70-85℃ and 30-45% relative humidity for 1.5-3 hours, and finally vacuum dried at 85-105℃ and -0.06 to -0.09 MPa for 2-4 hours to obtain the dried catalyst precursor; S6: Program calcination: The dried catalyst precursor is first heated to 180-220℃ in a nitrogen atmosphere at a rate of 1-2℃ / min and held for 1-2 hours. Then, it is heated to 260-320℃ in a nitrogen-oxygen mixture with an oxygen volume fraction of 2-5% and held for 1-2 hours. Finally, it is heated to 420-480℃ in air and held for 2-4 hours to obtain the residue oil hydrotreating catalyst.

[0007] Further, the polycarboxylic acid pore-regulating solution is prepared by the following method: 15-25% by mass of tetrasodium iminodisuccinate is added to the lactobionic acid pretreatment solution, and the mixture is stirred at 30-40℃ and 300-500 rpm for 20-40 min. Then, 8-15% by mass of gluconate-δ-lactone is added, and the mixture is stirred for another 20-30 min to prepare the polycarboxylic acid pore-regulating solution.

[0008] Further, the lactobionic acid pretreatment solution is prepared by the following method: adding 4-6 times its mass of deionized water to lactobionic acid, stirring at 25-35℃ and 300-500 rpm for 20-40 min, adding sodium bicarbonate accounting for 22-26% of the mass of lactobionic acid in batches, and continuing to stir at 30-40℃ for 40-60 min to obtain the lactobionic acid pretreatment solution.

[0009] Further, the nickel complexing additive solution is prepared by the following method: adding 5-8 times its mass of deionized water to tetrasodium glutamate diacetate, stirring at 25-35℃ and 300-500 rpm for 20-30 min, then adding 20-35% sodium gluconate and 5-10% ammonium acetate by mass of tetrasodium glutamate diacetate, and stirring at 40-50℃ and 400-600 rpm for 30-50 min to obtain the nickel complexing additive solution.

[0010] Further, in step S4, nickel nitrate hexahydrate is first added to the nickel complexing additive solution and stirred at 40-50℃ and 300-500rpm for 20-30min to obtain a metal mixture. Then, the metal mixture is added to an ammonium heptamolybdate solution and stirred at 40-55℃ and 400-600rpm for 20-40min. The pH is adjusted to 4.8-5.8 with 5-8% ammonia water to obtain an impregnation solution. The impregnation solution is divided into two equal parts. After the first part is sprayed, it is allowed to stand at 20-35℃ for 30-60min, and then the second part of the impregnation solution is sprayed. The nickel complexing additive solution is used to form a stable liquid phase system with the nickel component before the molybdenum component is introduced, so as to reduce the local enrichment of nickel and molybdenum components during the subsequent impregnation and drying process.

[0011] Furthermore, after the S2 treatment is completed, the obtained material is first allowed to drain naturally for 1-3 minutes, and then filtered under -0.04 to -0.06 MPa conditions for 1-3 minutes. After the filtration is completed, the S3 treatment is carried out within 30 minutes.

[0012] Furthermore, in step S3, the ammonium bicarbonate aqueous solution is sprayed in 2-3 times, and the mass of the ammonium bicarbonate aqueous solution is 8-15% of the mass of the treatment carrier material.

[0013] Furthermore, in S4, the mass of nickel nitrate hexahydrate and nickel complexing additive is 45-75% and 20-35% of the mass of ammonium heptamolybdate tetrahydrate, respectively, and the mass of ammonium heptamolybdate tetrahydrate is 16-24% of the mass of the second carrier.

[0014] Furthermore, the residual oil hydrogenation catalyst prepared by the aforementioned process uses alumina as a support and nickel and molybdenum as active metal components, wherein the nickel content calculated as NiO is 2.0-4.5% and the molybdenum content calculated as MoO3 is 10-18%.

[0015] Furthermore, the aforementioned residue hydrotreating catalyst has a BET specific surface area of ​​140-230 m² / g, a total pore volume of 0.70-1.00 mL / g, and pores with a diameter of 10-30 nm accounting for 50-75% of the total pore volume.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, a local reconstruction process involving pore regulation and pore structure fixation is implemented after the initial calcination of the alumina support. A multi-carboxyl-based regulating liquid is used to perform limited complexation treatment on the narrow pore regions that restrict macromolecular diffusion in the alumina support and on the Al-OH sites on the pore wall surface. Then, ammonium bicarbonate is used to regulate the local liquid phase environment within the pores, followed by high-temperature placement. This facilitates the redistribution and fixation of complexed aluminum species in the pore wall regions, thus forming a regulatory process of local pore treatment, species migration within the pores, and pore structure fixation. Compared to simply enlarging the overall pore size, this process can preferentially improve the narrow pores that restrict the diffusion of asphaltenes and macromolecular components in residual oil, enhancing pore connectivity and effective mass transfer capacity, while reducing damage to the support skeleton caused by excessive acid etching. This approach is beneficial for balancing the macroporous mass transfer performance and mechanical stability of the catalyst.

[0017] 2. In this invention, a complexing impregnation process is adopted, which involves pre-complexing the nickel component, introducing the molybdenum component later, and spraying in stages. First, nickel nitrate and the nickel complexing additive solution form a relatively stable metal mixture. Then, this mixture is introduced into the ammonium heptamolybdate system, and the pH of the impregnation solution is controlled. Components such as glutamic acid diacetate and glucohepanoate in the nickel complexing additive solution can provide a milder complexing environment for the nickel component, slowing down the rapid local deposition of nickel and molybdenum components during the impregnation process. Combined with two spraying processes, the phenomenon of concentrated enrichment of active metals in local areas of the carrier can be further reduced, allowing the Ni and Mo components to enter the carrier pores more fully and improving their dispersion uniformity. This reduces the aggregation of large-sized metal salts and pore blockage during subsequent drying and calcination, which is beneficial to improving the effective utilization of active metals.

[0018] 3. In this invention, a gradient drying process involving high humidity homogenization, gradient dehumidification, and low-pressure final drying is employed. The impregnated wet catalyst is first slowly homogenized under high relative humidity conditions, allowing sufficient time for the Ni and Mo components within the pores to re-adsorb and reach equilibrium. Then, the ambient humidity is gradually reduced, culminating in vacuum drying. This avoids the strong capillary flow caused by preferential evaporation of moisture from the outer surface of the particles during direct high-temperature rapid drying. This significantly reduces the tendency of Ni and Mo salts to migrate with the liquid phase towards the outer layer of the catalyst particles, improves the uniformity of the active metal distribution along the particle radial direction, and reduces the possibility of metal salt concentration and crystallization at the pore openings, as well as the formation of large-sized MoO3 aggregates during subsequent calcination. This reduces pore blockage and provides favorable conditions for the subsequent formation of highly dispersed hydrogenation active components. Attached Figure Description

[0019] Figure 1 The present invention provides a flowchart of a residue oil hydrogenation catalyst and its preparation process. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] It should be noted that the raw materials used in the following embodiments are all commercially available.

[0022] Example 1

[0023] Preparation of hydrogenation catalysts for residual oil: S1: Carrier molding: Boehmite and guar gum powder are mixed at a mass ratio of 100:2. Deionized water of 55% of the mass of boehmite and nitric acid aqueous solution of 12% of the mass of boehmite and 5% by mass fraction are added. The mixture is stirred at 300 rpm for 20 min, kneaded, extruded, dried at 100℃ for 6 h, and calcined at 520℃ for 3 h to obtain the first carrier. S2: Pore control treatment: Add 3.5 times its mass of deionized water and 2% of its mass of polycarboxylic acid pore control liquid to the first carrier, and treat at 50℃ and 60 rpm for 30 min. After treatment, filter and remove the free liquid on the surface of the first carrier to obtain the treated carrier material. S3: Pore structure fixation: Spray a 4% ammonium bicarbonate aqueous solution onto the treatment carrier material, place it at 60℃ and 85% relative humidity for 1 hour, wash it with deionized water at twice the mass of the treatment carrier material, dry it at 100℃ for 4 hours, and then calcine it at 450℃ for 2 hours to obtain the second carrier. S4: Complexation Impregnation: Add nickel nitrate hexahydrate to nickel complexation additive solution to obtain metal mixture solution, set aside for use. Dissolve ammonium heptamolybdate tetrahydrate in 2.5 times its mass of deionized water to obtain ammonium heptamolybdate solution. Add metal mixture solution to ammonium heptamolybdate solution and adjust pH to 4.8 with ammonia water to obtain impregnation solution. Spray the impregnation solution into the second carrier in two stages to obtain impregnated wet material. S5: Gradient drying: The impregnated wet material is placed at 35℃ and 88% relative humidity for 2 hours, then treated at 50℃ and 60% relative humidity for 1.5 hours, then treated at 70℃ and 30% relative humidity for 1.5 hours, and finally vacuum dried at 85℃ and -0.06MPa for 2 hours to obtain the dried catalyst precursor. S6: Program calcination: The dried catalyst precursor is first heated to 180°C at 1°C / min under a nitrogen atmosphere and held for 1 hour, then heated to 260°C in a nitrogen-oxygen mixture with 2% oxygen by volume and held for 1 hour, and finally heated to 420°C in air and held for 2 hours to obtain the residue oil hydrogenation catalyst.

[0024] In step S4, nickel nitrate hexahydrate is first added to a nickel complexing additive solution and stirred at 40°C and 300 rpm for 20 minutes to obtain a metal mixture. Then, the metal mixture is added to an ammonium heptamolybdate solution and stirred at 40°C and 400 rpm for 20 minutes. The pH is adjusted to 4.8 with 5% ammonia water to obtain an impregnation solution. The impregnation solution is divided into two equal parts. After the first part is sprayed, it is allowed to stand at 20°C for 30 minutes, and then the second part of the impregnation solution is sprayed.

[0025] After the S2 treatment is completed, the obtained material is first allowed to drain naturally for 1 minute, then filtered under -0.04 MPa conditions for 1 minute, and then the S3 treatment is carried out within 30 minutes after the filtration is completed.

[0026] In S3, the ammonium bicarbonate aqueous solution is sprayed in two stages, and the mass of the ammonium bicarbonate aqueous solution is 8% of the mass of the carrier material being treated.

[0027] In S4, the mass of nickel nitrate hexahydrate and nickel complex additive is 45% and 20% of the mass of ammonium heptamolybdate tetrahydrate, respectively, and the mass of ammonium heptamolybdate tetrahydrate is 16% of the mass of the second carrier.

[0028] Preparation of lactobionic acid pretreatment solution: Add 4 times the mass of deionized water to lactobionic acid, stir at 25℃ and 300 rpm for 20 min, add sodium bicarbonate accounting for 22% of the mass of lactobionic acid in batches, and continue stirring at 30℃ for 40 min to obtain lactobionic acid pretreatment solution.

[0029] Preparation of polycarboxylic acid pore conditioning solution: Add 15% by mass of tetrasodium iminodisuccinate to lactobionic acid pretreatment solution, stir at 30℃ and 300 rpm for 20 min, then add 8% by mass of gluconate-δ-lactone to lactobionic acid pretreatment solution, and continue stirring for 20 min to prepare polycarboxylic acid pore conditioning solution.

[0030] Preparation of nickel complexing additive solution: Add 5 times the mass of deionized water to tetrasodium glutamate diacetate and stir at 25℃ and 300 rpm for 20 min. Then add 20% sodium gluconate and 5% ammonium acetate by mass of tetrasodium glutamate diacetate and stir at 40℃ and 400 rpm for 30 min to obtain nickel complexing additive solution.

[0031] Example 2

[0032] Preparation of hydrogenation catalysts for residual oil: S1: Carrier molding: Boehmite and guar gum powder were mixed at a mass ratio of 100:2.5. Deionized water accounting for 65% of the mass of the boehmite and nitric acid aqueous solution accounting for 16% of the mass of the boehmite and having a mass fraction of 7% were added. The mixture was stirred at 450 rpm for 32 min, kneaded, extruded, dried at 112℃ for 8.5 h, and calcined at 565℃ for 4.5 h to obtain the first carrier. S2: Pore conditioning treatment: Add 4 times its mass of deionized water and 2.5% of its mass of polycarboxylic acid pore conditioning liquid to the first carrier, and treat at 55℃ and 80 rpm for 45 min. After the treatment is completed, filter and remove the free liquid on the surface of the first carrier to obtain the treated carrier material. S3: Pore structure fixation: Spray a 6.5% ammonium bicarbonate aqueous solution onto the treatment carrier material, place it at 65℃ and 91% relative humidity for 1.5h, wash it with 2.5 times the mass of the treatment carrier material with deionized water, dry it at 110℃ for 6.5h, and then calcine it at 480℃ for 3h to obtain the second carrier. S4: Complexation Impregnation: Add nickel nitrate hexahydrate to nickel complexation additive solution to obtain metal mixture solution, set aside for use. Dissolve ammonium heptamolybdate tetrahydrate in three times its mass of deionized water to obtain ammonium heptamolybdate solution. Add metal mixture solution to ammonium heptamolybdate solution and adjust pH to 5.0 with ammonia water to obtain impregnation solution. Spray the impregnation solution into the second carrier in two stages to obtain impregnated wet material. S5: Gradient drying: The impregnated wet material is placed at 40℃ and 92% relative humidity for 3 hours, then treated at 55℃ and 65% relative humidity for 2 hours, then treated at 75℃ and 35% relative humidity for 2 hours, and finally vacuum dried at 95℃ and -0.08MPa for 3 hours to obtain the dried catalyst precursor. S6: Program calcination: The dried catalyst precursor is first heated to 200℃ at 2℃ / min under a nitrogen atmosphere and held for 1.5h, then heated to 290℃ in a nitrogen-oxygen mixture with 3% oxygen volume and held for 1.5h, and finally heated to 460℃ in air and held for 3h to obtain the residue oil hydrogenation catalyst.

[0033] In step S4, nickel nitrate hexahydrate is first added to a nickel complexing additive solution and stirred at 46°C and 400 rpm for 25 min to obtain a metal mixture. The metal mixture is then added to an ammonium heptamolybdate solution and stirred at 48°C and 500 rpm for 30 min. The pH is adjusted to 5.0 with 6.5% ammonia water to obtain an impregnation solution. The impregnation solution is divided into two equal parts. After the first part is sprayed, it is allowed to stand at 28°C for 45 min before the second part of the impregnation solution is sprayed.

[0034] After the S2 treatment is completed, the obtained material is first allowed to drain naturally for 2 minutes, then filtered under -0.05MPa conditions for 2 minutes, and then the S3 treatment is carried out within 30 minutes after the filtration is completed.

[0035] In S3, the ammonium bicarbonate aqueous solution is sprayed in three separate applications, and the mass of the ammonium bicarbonate aqueous solution is 12% of the mass of the carrier material being treated.

[0036] In S4, the mass of nickel nitrate hexahydrate and nickel complex additive is 65% and 27% of the mass of ammonium heptamolybdate tetrahydrate, respectively, and the mass of ammonium heptamolybdate tetrahydrate is 20% of the mass of the second carrier.

[0037] Preparation of lactobionic acid pretreatment solution: Add 5 times the mass of deionized water to lactobionic acid, stir at 30℃ and 400 rpm for 30 min, add sodium bicarbonate accounting for 25% of the mass of lactobionic acid in batches, and continue stirring at 36℃ for 52 min to obtain lactobionic acid pretreatment solution.

[0038] Preparation of polycarboxylic acid pore conditioning solution: Add 21% of the mass of tetrasodium iminodisuccinate to the lactobionic acid pretreatment solution, stir at 36℃ and 400 rpm for 30 min, then add 12% of the mass of gluconate-δ-lactone to the lactobionic acid pretreatment solution, and continue stirring for 26 min to prepare the polycarboxylic acid pore conditioning solution.

[0039] Preparation of nickel complexing additive solution: Add 6.5 times the mass of deionized water to tetrasodium glutamate diacetate and stir at 32℃ and 400 rpm for 26 min. Then add sodium gluconate (25% by mass of tetrasodium glutamate diacetate) and ammonium acetate (7% by mass) and stir at 45℃ and 500 rpm for 40 min to obtain nickel complexing additive solution.

[0040] Example 3

[0041] Preparation of hydrogenation catalysts for residual oil: S1: Carrier molding: Boehmite and guar gum powder are mixed at a mass ratio of 100:4. Deionized water of 75% of the mass of boehmite and nitric acid aqueous solution of 20% of the mass of boehmite and 10% by mass fraction are added. The mixture is stirred at 500 rpm for 40 min, kneaded, extruded, dried at 120℃ for 10 h, and calcined at 580℃ for 5 h to obtain the first carrier. S2: Pore conditioning treatment: Add 5.5 times its mass of deionized water and 4% of its mass of polycarboxylic acid pore conditioning liquid to the first carrier, and treat at 65℃ and 100rpm for 60min. After the treatment is completed, filter and remove the free liquid on the surface of the first carrier to obtain the treated carrier material. S3: Pore structure fixation: Spray an 8% ammonium bicarbonate aqueous solution onto the treatment carrier material, place it at 75°C and 95% relative humidity for 2 hours, wash it with deionized water at 3 times the mass of the treatment carrier material, dry it at 120°C for 8 hours, and then calcine it at 520°C for 4 hours to obtain the second carrier. S4: Complexation Impregnation: Add nickel nitrate hexahydrate to the nickel complexation additive solution to obtain a metal mixture, set aside for use. Dissolve ammonium heptamolybdate tetrahydrate in 4.5 times its mass of deionized water to obtain an ammonium heptamolybdate solution. Add the metal mixture to the ammonium heptamolybdate solution and adjust the pH to 4.8-5.8 with ammonia water to obtain an impregnation solution. Spray the impregnation solution into the second carrier in two stages to obtain the impregnated wet material. S5: Gradient drying: The impregnated wet material is placed at 45℃ and 95% relative humidity for 4 hours, then treated at 65℃ and 75% relative humidity for 3 hours, then treated at 85℃ and 45% relative humidity for 3 hours, and finally vacuum dried at 105℃ and -0.09MPa for 4 hours to obtain the dried catalyst precursor. S6: Program calcination: The dried catalyst precursor is first heated to 220°C at 2°C / min under a nitrogen atmosphere and held for 2 hours, then heated to 320°C in a nitrogen-oxygen mixture with 5% oxygen by volume and held for 2 hours, and finally heated to 480°C in air and held for 4 hours to obtain the residue oil hydrogenation catalyst.

[0042] In step S4, nickel nitrate hexahydrate is first added to a nickel complexing additive solution and stirred at 50°C and 500 rpm for 30 minutes to obtain a metal mixture. Then, the metal mixture is added to an ammonium heptamolybdate solution and stirred at 55°C and 600 rpm for 40 minutes. The pH is adjusted to 5.8 with 8% ammonia water to obtain an impregnation solution. The impregnation solution is divided into two equal parts. After the first part is sprayed, it is allowed to stand at 35°C for 60 minutes, and then the second part of the impregnation solution is sprayed.

[0043] After the S2 treatment is completed, the obtained material is first allowed to drain naturally for 3 minutes, then filtered under -0.06MPa conditions for 3 minutes, and then the S3 treatment is carried out within 30 minutes after the filtration is completed.

[0044] In S3, the ammonium bicarbonate aqueous solution is sprayed in three stages, and the mass of the ammonium bicarbonate aqueous solution is 15% of the mass of the carrier material being treated.

[0045] In S4, the mass of nickel nitrate hexahydrate and nickel complex additive is 75% and 35% of the mass of ammonium heptamolybdate tetrahydrate, respectively, and the mass of ammonium heptamolybdate tetrahydrate is 24% of the mass of the second carrier.

[0046] Preparation of lactobionic acid pretreatment solution: Add 6 times the mass of deionized water to lactobionic acid, stir at 35℃ and 500 rpm for 40 min, add sodium bicarbonate accounting for 26% of the mass of lactobionic acid in batches, and continue stirring at 40℃ for 60 min to obtain lactobionic acid pretreatment solution.

[0047] Preparation of polycarboxylic acid pore conditioning solution: Add 25% by mass of tetrasodium iminodisuccinate to lactobionic acid pretreatment solution, stir at 40℃ and 500 rpm for 40 min, then add 15% by mass of gluconate-δ-lactone to lactobionic acid pretreatment solution, and continue stirring for 30 min to prepare polycarboxylic acid pore conditioning solution.

[0048] Preparation of nickel complexing additive solution: Add 8 times the mass of deionized water to tetrasodium glutamate diacetate and stir at 35℃ and 500 rpm for 30 min. Then add sodium gluconate (35% by mass of tetrasodium glutamate diacetate) and ammonium acetate (10% by mass). Stir at 50℃ and 600 rpm for 50 min to obtain nickel complexing additive solution.

[0049] Comparative Example 1 differs from Example 1 in that: this comparative example does not employ the S2 pore channel control treatment and the S3 pore structure fixing process, but instead uses a common pore-expanding agent for pore expansion; specifically, during the S1 carrier molding process, boehmite, guar gum powder, and deionized water are mixed, and polyethylene glycol accounting for 5% of the mass of boehmite is added as a pore-expanding agent, followed by a 5% mass fraction of nitric acid aqueous solution. The mixture is stirred at 300 rpm for 20 min, kneaded, extruded, dried at 100°C for 6 h, and then calcined at 520°C for 3 h, so that the polyethylene glycol is removed by calcination to form pores, thus obtaining the pore-expanded carrier; the obtained pore-expanded carrier is directly subjected to S4 complexation impregnation, and the subsequent S4-S6 and other raw material compositions, raw material amounts, and preparation conditions are the same as in Example 1.

[0050] Comparative Example 2 differs from Example 1 in that: in Comparative Example S4, the process of "pre-complexing of nickel components - subsequent introduction of molybdenum components - multiple spray impregnation" is not used. Instead, ammonium heptamolybdate tetrahydrate, nickel nitrate hexahydrate and nickel complexing additive are directly mixed and adjusted to the same pH as in Example 1. The resulting impregnation solution is then sprayed into the second carrier in one step.

[0051] Comparative Example 3 differs from Example 1 in that: in Comparative Example S5, high-humidity homogenization, gradient dehumidification and low-pressure final drying processes are not used. The impregnated wet material obtained in S4 is directly dried at 100°C and atmospheric pressure for 6 hours to obtain the dried catalyst precursor. The composition of other raw materials, the amount of raw materials used and the preparation conditions are the same as in Example 1.

[0052] Comparative Example 4 differs from Example 1 in that: no multi-carboxylic acid pore-regulating liquid is added in Comparative Example S2; only the first carrier is added to the same amount of deionized water as in Example 1 and treated under the same temperature, rotation speed and time conditions. Subsequently, filtration and S3 pore structure fixation are performed according to Example 1. The composition of other raw materials, the amount of raw materials used and the preparation conditions are the same as in Example 1.

[0053] Comparative Example 5 differs from Example 1 in that: after completing the S2 channel conditioning treatment, ammonium bicarbonate aqueous solution was sprayed in accordance with Example 1 to adjust the pH of the residual treatment solution in the pore, but the high humidity placement process in S3 was cancelled. After spraying, deionized water was used for cleaning, followed by drying and calcination. The composition of other raw materials, the amount of raw materials used, and the preparation conditions were the same as in Example 1.

[0054] Comparative Example 6 differs from Example 1 in that: no nickel complexing additive is added to this comparative example; nickel nitrate hexahydrate is added to an equal amount of deionized water as the nickel complexing additive; the mixture is stirred under the same conditions as in Example 1; then ammonium heptamolybdate solution is added and the mixture is sprayed twice as in Example 1; the composition of other raw materials, the amount of raw materials used, and the preparation conditions are the same as in Example 1.

[0055] Comparative Example 7 differs from Example 1 in that: in Comparative Example S6, no programmed roasting is used; the dried catalyst precursor obtained in S5 is directly placed in an air atmosphere and kept at 450°C for 3 hours to obtain a residue oil hydrogenation catalyst; the composition of other raw materials, the amount of raw materials used, and the preparation conditions are the same as in Example 1.

[0056] Nitrogen adsorption-desorption test: Nitrogen adsorption-desorption tests were conducted on the residue hydrotreating catalysts prepared in Examples 1-3, according to GB / T 21650.2-2008. Before the test, the catalyst samples were degassed to remove moisture and other substances adsorbed on the pores and surface. Nitrogen was used as the adsorbate during the test. The pore structure parameters of the catalyst were obtained through adsorption-desorption isotherms. The specific surface area was calculated using the BET method, the total pore volume was calculated based on the adsorption amount, and the cumulative pore volume within the 10-30 nm pore size range and the proportion of this cumulative pore volume to the total pore volume were calculated based on the pore size distribution results. The test data are shown in Table 1 below: Table 1

[0057] Determination of active metal component content: The residue oil hydrotreating catalysts prepared in Examples 1-3 were ground and digested. The actual mass content of nickel and molybdenum in the catalysts was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). Each sample was measured in triplicate, and the arithmetic mean of the three test results was taken as the final result. Based on the measured mass content of nickel and molybdenum, the nickel component content (calculated as nickel oxide) and the molybdenum component content (calculated as molybdenum trioxide) were calculated according to the relative molecular masses of nickel oxide and molybdenum trioxide, respectively. The test data are shown in Table 2 below: Table 2

[0058] As can be seen from the above test results, the nickel content (calculated as NiO) and molybdenum content (calculated as MoO3) of the residue hydrotreating catalysts obtained in Examples 1-3 are within the product composition range defined in this application; the BET specific surface area, total pore volume, and pore volume ratio of 10-30 nm pore size of the catalysts obtained in Examples 1-3 are also within the pore structure parameters range defined in this application.

[0059] Performance testing: The performance of the residue hydrotreating catalysts treated in Examples 1-3 and Comparative Examples 1-7 was tested, and the test data are recorded in Table 3 below: Table 3

[0060] In the performance test, the pore volume ratio of 10 to 30 nanometers was determined as follows: referring to GB / T 21650.2-2008, the pore size distribution of the residue hydrotreating catalysts obtained in the examples and comparative examples was tested. Based on the obtained pore size distribution data, the cumulative pore volume and total pore volume in the 10 to 30 nanometer range were calculated respectively, and the percentage of the former to the latter was used as the test result.

[0061] Determination of radial distribution deviation of active metals: Ten catalyst particles were randomly selected, and each catalyst was cut along a direction perpendicular to its axis to prepare a flat cross-section. Elemental analysis was performed using scanning electron microscopy-energy dispersive spectroscopy (EDS) according to GB / T 17359-2023. Seven test areas, each with an area of ​​2500 μm², were equidistantly set from one outer edge to the other along one diameter of the cross-section of each particle. The mass fractions of Ni and Mo were measured, and the average value of the test results for the ten catalysts was taken as the final result.

[0062] Determination of average crushing force: Ten residue hydrotreating catalysts were randomly selected for testing. The sample diameter was 0.3 cm, and each sample was cut into 0.5 cm long segments. Radial loading was applied according to the particle crushing force determination method in GB / T 33068-2016. The maximum load at failure of each sample was recorded, and the crushing force of a single sample was calculated as the ratio of the maximum load at failure to the sample length, in N / cm. Ten samples were tested for each sample, and the arithmetic mean of the test results of the ten samples was taken as the average crushing force of the sample.

[0063] As shown in Table 3 of the performance test data, the pore volume ratio of the residue hydrotreating catalysts prepared in Examples 1-3 (10-30 nm) is generally higher than that in Comparative Examples 1, 4, and 5, while maintaining good particle crushing resistance. This indicates that the "pore channel regulation treatment - pore structure fixation" process adopted in this invention can maintain the stability of the support skeleton while improving the pore structure of the support. The multi-carboxyl weak complexing system formed by the multi-carboxyl pore channel regulation liquid can perform limited complexation and local treatment on the highly active aluminum hydroxyl regions in narrow pore areas. Subsequently, the residual treatment liquid in the pores is adjusted by ammonium bicarbonate and the pores are placed under high humidity, allowing the migrated aluminum species to redistribute and be fixed in the larger pore wall areas. In contrast, while Comparative Example 1, using a common pore-expanding agent, can increase the number of pores to a certain extent, its pore-expanding process lacks selectivity for narrow channels, easily leading to thinning of some pore walls and reduced continuity of the carrier skeleton, thus decreasing the particle's crushing resistance. Comparative Example 4, without using a multi-carboxyl pore-controlling liquid, struggles to achieve selective pore-controlling treatment. In Comparative Example 5, after eliminating the high-humidity fixation process, the migrated aluminum species cannot be fully redeposited, which is also detrimental to pore wall structure stability. This demonstrates that the present invention, by combining limited pore-controlling treatment with pore wall re-fixation, achieves a synergistic improvement in pore connectivity and mechanical stability, solving the problem of balancing pore structure improvement and carrier strength in conventional pore-expanding processes.

[0064] Furthermore, the radial distribution deviation of the active metal in the residue hydrotreating catalysts prepared in Examples 1-3 was significantly lower than that in Comparative Examples 2, 3, and 6, indicating that the "nickel component pre-complexation—molybdenum component post-introduction—multi-stage spray impregnation" process and subsequent gradient drying process adopted in this invention can effectively improve the distribution state of nickel and molybdenum active components within the catalyst particles. The glutamic acid diacetate and glucohepanoate in the nickel complexing addition solution can provide a relatively stable liquid-phase complexing environment for the nickel component, ensuring good dispersion of the nickel component before the addition of the molybdenum component. Combined with the subsequent introduction of the molybdenum component and multi-stage spray impregnation, the active metal gradually enters the internal pores of the support. In Comparative Example 2, after changing the pre-complexing and multi-stage spraying methods, the active metal was more likely to form a concentration gradient in local areas. In Comparative Example 6, after removing the nickel complexing additive, the nickel component lacked the corresponding liquid-phase stabilizing effect, leading to an increase in local enrichment during subsequent impregnation. Although Comparative Example 3 retained the initial complexing impregnation process, it directly carried out high-temperature drying. The capillary migration caused by the preferential evaporation of moisture from the outer layer of the particles carried the soluble metal components to the outside, resulting in a more obvious radial distribution difference. Therefore, this invention, through the continuous combination of pre-complexing impregnation and gradient drying, reduces the tendency of active metal to migrate to the outer layer of the particles and locally accumulate during impregnation and drying, solving the problem of "outer layer enrichment and inner layer depletion" of active metal in traditional impregnation and drying processes.

[0065] By comparing and analyzing the relevant data in Table 3, it can be seen that the present invention, through the synergistic effect of processes such as local reconstruction of narrow pore regions, complexation impregnation, and gradient drying, improves the effective pore structure of the catalyst, enhances the uniformity of the distribution of nickel and molybdenum active components within the support, maintains good support mechanical stability, and reduces the migration and aggregation of active metals and pore blockage. This indicates that the residue oil hydrogenation catalyst prepared by the present invention has good comprehensive performance and application value.

[0066] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0067] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A process for preparing a residue oil hydrogenation catalyst, characterized in that, Includes the following steps: S1: Carrier molding: Boehmite and guar gum powder are mixed at a mass ratio of 100:(2-4), and 55-75% of the mass of boehmite in deionized water and 12-20% of the mass of boehmite in nitric acid aqueous solution with a mass fraction of 5-10% are added. The mixture is stirred at 300-500 rpm for 20-40 min, kneaded, extruded, dried at 100-120℃ for 6-10 h, and calcined at 520-580℃ for 3-5 h to obtain the first carrier; S2: Pore control treatment: Add 3.5-5.5 times its mass of deionized water and 2-4% of its mass of polycarboxylic acid pore control solution to the first carrier, and treat at 50-65℃ and 60-100rpm for 30-60min. After treatment, filter and remove the free liquid on the surface of the first carrier to obtain the treated carrier material. The polycarboxylic acid pore control solution is prepared by mixing lactobionic acid pretreatment solution, tetrasodium iminodisuccinate and gluconate-δ-lactone in aqueous phase. S3: Pore structure fixation: Spray 4-8% ammonium bicarbonate aqueous solution onto the treatment carrier material, place it at 60-75℃ and 85-95% relative humidity for 1-2 hours, wash it with 2-3 times the mass of deionized water, dry it at 100-120℃ for 4-8 hours, and then calcine it at 450-520℃ for 2-4 hours to obtain the second carrier; S4: Complexation Impregnation: Nickel nitrate hexahydrate is added to the nickel complexation additive solution to obtain a metal mixture solution, which is set aside for use. Ammonium heptamolybdate tetrahydrate is dissolved in 2.5-4.5 times its mass of deionized water to obtain an ammonium heptamolybdate solution. The metal mixture solution is added to the ammonium heptamolybdate solution, and the pH is adjusted to 4.8-5.8 with ammonia water to obtain an impregnation solution. The impregnation solution is sprayed into the second carrier in two stages to obtain the impregnated wet material. The nickel complexation additive solution is prepared by mixing tetrasodium diacetate of glutamic acid, sodium gluconate and ammonium acetate in an aqueous phase. S5: Gradient drying: The impregnated wet material is placed at 35-45℃ and 88-95% relative humidity for 2-4 hours, then treated at 50-65℃ and 60-75% relative humidity for 1.5-3 hours, then treated at 70-85℃ and 30-45% relative humidity for 1.5-3 hours, and finally vacuum dried at 85-105℃ and -0.06 to -0.09 MPa for 2-4 hours to obtain the dried catalyst precursor; S6: Program calcination: The dried catalyst precursor is first heated to 180-220℃ in a nitrogen atmosphere at a rate of 1-2℃ / min and held for 1-2 hours. Then, it is heated to 260-320℃ in a nitrogen-oxygen mixture with an oxygen volume fraction of 2-5% and held for 1-2 hours. Finally, it is heated to 420-480℃ in air and held for 2-4 hours to obtain the residue oil hydrotreating catalyst.

2. The preparation process of the residue hydrotreating catalyst according to claim 1, characterized in that, The polycarboxylic acid pore-regulating solution is prepared by the following method: 15-25% of the mass of tetrasodium iminodisuccinate is added to the lactobionic acid pretreatment solution, and the mixture is stirred at 30-40℃ and 300-500 rpm for 20-40 min. Then, 8-15% of the mass of gluconate-δ-lactone is added, and the mixture is stirred for another 20-30 min to obtain the polycarboxylic acid pore-regulating solution.

3. The preparation process of the residue hydrotreating catalyst according to claim 2, characterized in that, The lactobionic acid pretreatment solution is prepared by the following method: adding 4-6 times the mass of deionized water to lactobionic acid, stirring at 25-35℃ and 300-500rpm for 20-40min, adding sodium bicarbonate in batches at 22-26% of the mass of lactobionic acid, and continuing to stir at 30-40℃ for 40-60min to obtain the lactobionic acid pretreatment solution.

4. The preparation process of the residue hydrotreating catalyst according to claim 3, characterized in that, The nickel complexing additive solution is prepared by the following method: adding 5-8 times its mass of deionized water to tetrasodium glutamate diacetate, stirring at 25-35℃ and 300-500 rpm for 20-30 min, then adding 20-35% sodium gluconate and 5-10% ammonium acetate by mass of tetrasodium glutamate diacetate, and stirring at 40-50℃ and 400-600 rpm for 30-50 min to obtain the nickel complexing additive solution.

5. The preparation process of the residue hydrotreating catalyst according to claim 1, characterized in that, In step S4, nickel nitrate hexahydrate is first added to the nickel complexing additive solution and stirred at 40-50℃ and 300-500rpm for 20-30min to obtain a metal mixture. Then, the metal mixture is added to ammonium heptamolybdate solution and stirred at 40-55℃ and 400-600rpm for 20-40min. The pH is adjusted to 4.8-5.8 with 5-8% ammonia water to obtain an impregnation solution. The impregnation solution is divided into two equal parts. After the first part is sprayed, it is allowed to stand at 20-35℃ for 30-60min before the second part of the impregnation solution is sprayed.

6. The preparation process of the residue hydrotreating catalyst according to claim 1, characterized in that, After the S2 treatment is completed, the obtained material is first allowed to drain naturally for 1-3 minutes, and then filtered under -0.04 to -0.06 MPa conditions for 1-3 minutes. After the filtration is completed, the S3 treatment is carried out within 30 minutes.

7. The preparation process of the residue hydrotreating catalyst according to claim 1, characterized in that, The ammonium bicarbonate aqueous solution in S3 is sprayed in 2-3 times, and the mass of the ammonium bicarbonate aqueous solution is 8-15% of the mass of the treatment carrier material.

8. The preparation process of the residue hydrotreating catalyst according to claim 1, characterized in that, In S4, the mass of nickel nitrate hexahydrate and nickel complex additive is 45-75% and 20-35% of the mass of ammonium heptamolybdate tetrahydrate, respectively, and the mass of ammonium heptamolybdate tetrahydrate is 16-24% of the mass of the second carrier.

9. A residue hydrotreating catalyst prepared by the process described in any one of claims 1-8, characterized in that, Using alumina as a carrier, nickel and molybdenum are the active metal components, wherein the nickel content, calculated as NiO, is 2.0-4.5%, and the molybdenum content, calculated as MoO3, is 10-18%.

10. The residue hydrotreating catalyst according to claim 9, characterized in that, Its BET specific surface area is 140-230m² / g, the total pore volume is 0.70-1.00mL / g, and the pore volume with a pore size of 10-30nm accounts for 50-75% of the total pore volume.

Citation Information

Patent Citations

  • Hydrodemetallization catalyst for residue oil and its preparation method

    CN106914249B

  • Slag oil hydro-demetallization catalyst and its preparing method

    CN1782031A